Interactive Infographics in Religious Education: A Needs Assessment for Junior High School Students - Januri Januri; Makmum Raharjo; Dwi Hasmidyani (STAI Hubbulwathan Duri, 2025)
Religious education plays a crucial role in shaping students' moral character. However, traditional teaching methods often fail to engage students effectively. This study investigates the potential of interactive infographic-based learning media in enhancing students’ understanding of religious concepts and fostering respect for parents and teachers. This qualitative-descriptive study was conducted at SMP IT Darussalam Lahat with 35 students, 4 teachers, and 6 parents. Data were collected through 12 semi-structured interviews, classroom observations over three months, and documentation analysis. Thematic coding was employed to analyze media effectiveness, student engagement, and character development. Findings indicate a strong need for interactive and visually engaging media in religious education. Respondents emphasized that infographic-based learning materials enhanced student comprehension and engagement. Teachers and parents observed improvements in students’ attitudes, particularly in showing respect towards parents and teachers. The results highlight the effectiveness of interactive infographics in making religious education more accessible and engaging. By integrating visual and interactive elements, students develop a deeper understanding and stronger connection to religious values. This study suggests that incorporating such media can significantly enhance moral education outcomes. Interactive infographic-based media effectively supports religious character development by improving comprehension and engagement. The study provides insights for future research and the broader application of digital media in religious education.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//